Правова культура як основний складник професійної культури юриста - Чупринський, Б. О.; Chuprynskyy, B. O. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Статтю присвячено дослідженню правової культури як основного складника професійної культури юриста. Професійна культуру юриста проаналізовано як певний різновид субкультури, що «вбирає» в себе елементи різних видів культур. The article investigates the legal culture as a key component of the professional culture of lawyers. Professional culture of a lawyer is seen as some kind of subculture that absorbs the elements of different types of cultures. The main component that forms the professional culture of a lawyer is his professional consciousness, which directly affects the nature of the professional activity.
Corporate Culture as a Core Component of Professional Culture Lawyer
Keywords: філософія права; philosophy of law; правова культура; legal culture; правова свідомість; legal consciousness; професійна діяльність; professional activity; профе-сійна культура; professional culturе